Seismic Behavior of Steel Storage Pallet Racking Systems - Castiglioni, Carlo Andrea; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents the main outcomes of the first European research project on the seismic behavior of adjustable steel storage pallet racking systems. In particular, it describes a comprehensive and unique set of full-scale tests designed to assess such behavior. The tests performed include cyclic tests of full-scale rack components, namely beam-to-upright connections and column base connections; static and dynamic tests to assess the friction factor between pallets and rack beams; full-scale pushover and pseudodynamic tests of storage racks in down-aisle and cross-aisle directions; and full-scale dynamic tests on two-bay, three-level rack models. The implications of the findings of this extensive testing regime on the seismic behavior of racking systems are discussed in detail, highlighting e.g. the confirmation that under severe dynamic conditions "sliding" is the main factor influencing rack response. This work was conceived during the development of the SEISRACKS project. Its outcomes will contribute significantly to increasing our knowledge of the structural behavior of racks under earthquake conditions and should inform future rack design.
Introduction -- Component Tests -- Pallet Sliding -- Pushover Tests -- Pseudodynamic Tests -- Dynamic Full-Scale Tests -- Conclusions. .
Keywords: Light construction; Steel construction; Lightweight construction; Building materials; Mechanics, Applied; Solids; Materials -- Analysis; Sustainability; Light-weight Construction, Steel and Timber Construction; Structural Materials; Solid Mechanics; Characterization and Analytical Technique; Sustainability